PENCEGAHAN KOROSI DENGAN BOILER WATER TREATMENT (BWT) PADA KETEL UAP KAPAL. - Suleman, Suleman (Department of Naval Architecture - Diponegoro University, 2007)
This paper explained about a using of Boiler Water Treatment (BWT) as corrosion protection for boiler on ship. BWT used as addition on boiler water, which used destilat water. As experiment results, BWT used on destilat water and destilat - seawater mixed given not koagulan patch on. The simulation given not satisfied results, caused by good not equipment.